PENGARUH BRAND AMBASSADOR DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PENGGUNA ERIGO DI KOTA SURABAYA - Muhammad Ali Akbar Jasmine; Yosi Afandi (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
This research was quantitative This study used primary data taken from questionnaires distributed to 102 respondens obtained through the purposive sampling technique. The responden were customer who purchased Erigo products. The data analysis of this study used multiple regression analysis. The free variable consist of of Brand Ambassador and Price while the bound variable was the purchase decision. The results of this study showed that Brand Ambassadors influence the purchasing decisions. The prices affect the purchase decisions. The product quality and price affect purchasing decisions at Erigo in Surabaya City. Based on the results of this study, Erigo should increase the quality and prices because the variables Brand Ambassador and price have a dominant influence in influencing the purchasing decisions. and it can influence consumers to buy. From the results of this study, it can be concluded that Erigo has used Arif Muhammad to lure consumers to make purchases at prices that can be reached by consumers, so that it can influence purchasing decisions